The impact of vocational education and training on company performance - (:unkn) unknown (Publications Office of the European Union, 2011)
"This study is a meta-analysis of the evidence available in literature on the economic benefits of VET at company level. It is based on 62 studies and 264 estimated effects, covering many different company performance and training indicators. The meta-analysis concludes that VET has a positive and significant effect on the economic performance of firms. This result is valid for most performance indicators and VET indicators, and is also robust to the methodology used in the studies. Evidence on the effects of different types of training is limited because this aspect is not recorded in most of the studies. Similarly, a clear relationship between size of investment and size of the effect on productivity was hard to establish for the limited comparability of the VET variables and estimated effects collected." (Hrsg., BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 1.5.3 Betriebliche Weiterbildung; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; I 2.2 Europa; Betriebliche Berufsausbildung; Betriebliche Weiterbildung; Kosten-Nutzen-Analyse; Bildungsertrag; Indikatoren; Unternehmenserfolg; Metaanalyse; Europa